The Impact of Fireworks Emissions on Air Quality in Delhi, India. Issue 4 (1st October 2020) - Singh, Akash Kumar; Srivastava, Arun
Abstract: The present study was carried out during the Diwali fireworks period in the month of November over an urban site in Delhi, India. This article concludes that the burning of crackers and sparkles are a strong source of metals, organic carbon, elemental carbon and particulate matter pollution, and that firecrackers burning adversely affects ambient air quality. Morevoer, the release of certain toxic elements and gases such as aluminum, barium, strontium and chlorine can have particualry negative health affects on people suffering with respiratory ailements. Public awareness is needed to control air pollution caused due to the display of fireworks.